2015
DOI: 10.1589/jpts.27.2883
|View full text |Cite
|
Sign up to set email alerts
|

The role of visual feedback in respiratory muscle activation and pulmonary function

Abstract: [Purpose] It is well known that visual feedback is an important factor contributing to balance and postural control. Nevertheless, there has been little discussion about the effects of visual feedback on pulmonary function. This study was conducted to investigate the role of visual feedback on respiratory muscle activation and pulmonary function. [Subjects and Methods] The subjects were 37 healthy adults who consented to participate in this study. The study measured the muscular activation of the trunk and pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that VF is beneficial in increasing muscle contraction and muscle activation 5 , 6 ) . Park et al 7 ) reported that breathing exercise with VF improved pulmonary function and increased respiratory muscle activity. Prior studies demonstrated the effect of VF on various muscle activities but tongue muscle activity was never investigated previously.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that VF is beneficial in increasing muscle contraction and muscle activation 5 , 6 ) . Park et al 7 ) reported that breathing exercise with VF improved pulmonary function and increased respiratory muscle activity. Prior studies demonstrated the effect of VF on various muscle activities but tongue muscle activity was never investigated previously.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Park et al. 14 ) report breathing exercise using visual feedback can increase pulmonary function and respiration muscle activation significantly. Recently, this visual biofeedback is used to care the stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased respiratory capacity may be induced through activity limitation and restriction of the social participation of stroke patients 13 ) . In a study by Sandberg et al 4 ) , the participants of the experimental group had improved their respiratory capacity, walking endurance, and balance ability.…”
Section: Discussionmentioning
confidence: 99%